Review of The Implementations of Restaurant Tax Collection and Calculation at the Regional Revenue Agency of Padang City (BAPENDA Kota Padang) - Herfina, Melli (Dinasti Publisher, 2022)
The purpose of this study is to find out what system is used to implement restaurant tax collection and the calculations carried out by the Regional Revenue Agency of Padang City so that knowing the system applied will make it easier to increase local revenue.To obtain data and information, in this study adapted to the data collection method, the authors used interviews and observations. Primary data, the authors obtained from respondents, namely from employees of the Regional Revenue Agency of Padang City, while secondary data the authors obtained from the library by looking for books related to taxation.Our tax law adheres to self-assessment where taxpayers are given the trust to calculate and apply the amount of income owed and then report it to the tax counseling and consulting office after the tax year ends.